Sistem Tata Air, Kendala dan Potensi Lahan Rawa Lebak di Instalasi Penelitian dan Pengkajian Teknologi Pertanian (IP2TP) Kayuagung, Sumatera Selatan - Puspitahati, Puspitahati; Perdana, Agung; Handayani, Putri Natasya Anugrah; Rahmawati, Laila (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2024)
Lebak swamp land has the main problem in the condition of a fluctuating water regime and unpredictable water entry into the land. A review of the water system network is needed for the development of agricultural cultivation in the Lebak swamp. The purpose of this study is to determine the network of water systems, constraints and potentials in the swamp land of the Kayuagung Agricultural Technology Research and Assessment Installation, South Sumatra. This research was carried out at the Agricultural Technology Research and Assessment Installation, Kayuagung, South Sumatra with observation, interview, and literature study methods. The results of the study show that the IP2TP Kayuagung lebak swamp land is a confined lebak which is located far from the Komering River divided into 3 typologies, namely shallow lebak, middle lebak, and lebak dalam. The soil type in the IP2TP Kayuagung experimental garden is inceptisol, while the land type is suboptimal. The water management system of the Lebak swamp land at the Agricultural Technology Assessment and Research Installation (IP2TP) in Kayuagung uses a rainwater system and polders (mobile embankments) equipped with primary, tertiary and quaternary channels. Identification in the field there are obstacles in the management of the IP2TP Kayuagung lebak swamp land caused by the dependence of land water sources on rainfall so that it can only be planted once a year and during the rainy season the land will be submerged. The condition of the IP2TP lebak swamp land has been productive as agricultural cultivation land, both rice, palawija and even horticultural crops and can have the potential to cultivate several livestock such as ducks, chickens, cows or freshwater fish. It is necessary to make efforts to revitalize swamp land by making water can come out and flow into the river so that the water can recede in the dry season and food crops that have been tried can be cultivated again.